Définir les rituels à l'école maternelle : un paradoxe institutionnel, pédagogique et scientifique - Sophie Briquet-Duhazé (Nantes Université, 2015)
The term "ritual" signifies the rules and habits that organize the classroom life. They are repeated daily with a general objective of acquiring autonomy. These rituals are based on several parameters: space and time, competencies and specific objectives, manipulable material. Their repetition is built on activities, variating and evolving simulation exercises, in which every student contributes to the group's construction. We propose to question the paradox that exists between the extensive use of the term in kindergarten classrooms and it's virtual absence in official, educational and scientific literature.